Santri 5.0: Islamic Education In The Digital Era And Global Challenges In Mandailing - Nasution, Suryadi; Nur, Kholidah; Khairurrijal, Khairurrijal; Pohan, Ali Jusri (IAIN Pontianak, 2025)
This research explores the transformation of Islamic education in the digital era within the context of classical pesantren (Islamic boarding schools) in Mandailing Natal—namely Ma'had Darul Ikhlas, Raihanul Jannah, and Abinnur al-Islami—with a focus on the vision of “Santri 5.0.” Employing a multisite qualitative approach, the study reveals that traditional methods such as sorogan and bandongan remain dominant. However, 70-80% of santri (students) use mobile phones primarily for non-academic content, indicating cracks in the fortress of tradition. Social media emerges as a double-edged sword: 65% of santri utilize it for informal da'wah (Islamic outreach), while 40% are exposed to secular and radical narratives due to limited digital literacy. Although santri express a desire for innovation (50-60%), static curricula and institutional resistance to technology hinder integration, leaving the potential of “Santri 5.0” unfulfilled. This study concludes that without pedagogical adaptation, pesantren risk losing relevance in the global era, underscoring the urgency of developing Islamic education that is responsive to digital challenges while preserving local identity.